TERAPI FORGIVENESS UNTUK MENINGKATKAN SELF ESTEEM PADA REMAJA KORBAN PERSELINGKUHAN DALAM HUBUNGAN BERPACARAN - Zuroida, Aironi; Kireida Kusnadi, Starry; Milenia Putri, Futy Oktav (Universitas Darul Ulum, 2024)
Teenagers are individuals who are in puberty, during this period teenagers begin to feel attracted to the opposite sex and start dating. In a dating relationship it doesn't always run smoothly, one of the problems in a dating relationship is infidelity. The phenomenon of infidelity in teenagers results in teenagers having a negative self-evaluation, this happens because individuals who have been cheated on tend to feel rejected, have difficulty seeing themselves as valuable and need other people's opinions to accept themselves so that self-esteem decreases. One way to get rid of negative feelings is with forgiveness therapy. This research aims to determine the effectiveness of forgiveness therapy to increase the self-esteem of adolescent victims of infidelity. This research uses a quasi-experimental research design and uses a one group posttest-pretest technique with purposive sampling of subjects, namely teenagers aged 12-21 years who have had the experience of being cheated on and have not been able to forgive. Statistical tests were analyzed using Paired Sample T-Test. The results show a 2-tailed sig value of 0.004 < 0.005, which means that it is significant, giving Forgiveness Therapy is effective in increasing the self-esteem of Adolescent Victims of Infidelity so that they can be forgiving and able to minimize the tendency of decreasing self-esteem.